Persuasive Communication in the Development of Muslim Converts Religion - Tahir, Aswar (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
Muslim converts to Islam are non-Muslims who have hopes of embracing Islam or those who have converted to Islam. This article aims to describe persuasif communication in the religious development of Muslim converts. The method used in this research is descriptive qualitative method. Data collection was carried out through studies in electronic books and scientific articles as well as non-electronic articles according to the research theme. The results of this study indicate that the determination of strategies in persuasif communication planning is to designate da'i as communicators, recognize the condition of the audience or mad'u in this context are Muslim converts themselves, techniques for composing messages by conveying material Islamic values, media or tools used namely madrasas and mosques as well as information technology media, as well as using lecture, discussion and practice methods. In the religious development of Muslim converts through persuasif communication according to the AIDDA model, starting from the stage of building attention, interest, desire, decision, and action